Cloud enabled business model innovation: gaining strategic competitive advantage as the market emerges. (1st January 2014) - Brook, Jacques W.; Feltkamp, Vincent; van der Meer, Martin
Previous studies discussed cloud computing as a disruptive technology. Building from these studies, the aim of this research was to gain more understanding of the innovation of the business model of customers as a result of adopting cloud service delivery models. Our findings suggest that the adoption of cloud service delivery models is positively associated with new revenue source and the reduction of capital expenditure of information technology assets within the firm. However, the correlation between reducing operational expenditure and redesigning the value chain appears to be negative for instance. The current fragmented way of adopting cloud delivery models in different functional units limits the ability of firms to leverage cloud delivery models for a successful business model innovation. As the market structure is still emerging, customers need to pay attention to a better interaction between the variables in order to refine the business model innovation successfully over time.